2008
DOI: 10.1167/8.16.15
|View full text |Cite
|
Sign up to set email alerts
|

Visual memory during pauses between successive saccades

Abstract: Selective attention is closely linked to eye movements. Prior to a saccade, attention shifts to the saccadic goal at the expense of surrounding locations. Such a constricted attentional field, while useful to ensure accurate saccades, constrains the spatial range of high-quality perceptual analysis. The present study showed that the attention could be allocated to locations other than the saccadic goal without disrupting the ongoing pattern of saccades. Saccades were made sequentially along a color-cued path. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 87 publications
(108 reference statements)
6
29
1
Order By: Relevance
“…If an item has already been selected for memory because it is presented at the saccade target location, there should be no additional benefit because it is likewise selected for memory based on its property. Indeed, a strong reduction in spatial congruency effects due to better performance on incongruent trials has been reported previously in a memory task when the to be remembered stimulus was cued in advance (Gersch et al, 2008), albeit at a cost in saccade performance.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…If an item has already been selected for memory because it is presented at the saccade target location, there should be no additional benefit because it is likewise selected for memory based on its property. Indeed, a strong reduction in spatial congruency effects due to better performance on incongruent trials has been reported previously in a memory task when the to be remembered stimulus was cued in advance (Gersch et al, 2008), albeit at a cost in saccade performance.…”
Section: Discussionsupporting
confidence: 62%
“…In these experiments, the saccade target and the perceptual target were both colored and the color of the perceptual target varied randomly, matching the saccade target's color on a subset of trials. We found that perceptual targets incidentally matching the color of the saccade target were slightly easier to discriminate than perceptual targets not matching the color of the saccade target (see also Gersch et al, 2008Gersch et al, , 2009. The effect of color congruency did not interact with the effect of spatial congruency, that is, the two effects were additive.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous work has highlighted links between attention and memory as sequential eye movements are executed, demonstrating that the final target of an eye movement sequence is remembered better than any target that was previously attended along the path of the eye movement sequence (Gersch et al, 2008). The present study revealed greater activity in IT cortex when the previously attended location was suppressed in the IOR condition, suggesting a potential mechanism that allows data from the previously attended location to be suppressed so that data at the current location can be best encoded.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous work has indicated that attention and memory are linked during execution of sequential eye movements. This work demonstrated that visual short-term memory performance was best for the final target in an eye movement sequence, suggesting that there may be differential memory encoding for the final target versus those that were previously attended within the sequence (Gersch, Schnitzer, & Dosher, 2008). By comparing the noncued target trials across the IOR and Facilitation conditions in the present study, we examined whether suppression at a previously attended location might contribute to this enhancement in memory encoding.…”
Section: Introductionmentioning
confidence: 91%